Stress responses in flavivirus-infected cells: activation of unfolded protein response and autophagy - Blázquez, Ana-Belén; Escribano-Romero, Estela; Merino-Ramos, Teresa; Saiz, Juan-Carlos; Martín-Acebes, Miguel A. (Frontiers in Microbiology, 2014)
The Flavivirus is a genus of RNA viruses that includes multiple long known human, animal and zoonotic pathogens such as Dengue virus, yellow fever virus, West Nile virus or Japanese encephalitis virus, as well as other less known viruses that represent potential threats for human and animal health such as Usutu or Zika viruses. Flavivirus replication is based on endoplasmic reticulum-derived structures. Membrane remodeling and accumulation of viral factors induce endoplasmic reticulum stress that results in activation of a cellular signaling response termed unfolded protein response (UPR), which can be modulated by the viruses for their own benefit. Concomitant with the activation of the UPR, an upregulation of the autophagic pathway in cells infected with different flaviviruses has also been described. This review addresses the current knowledge of the relationship between endoplasmic reticulum stress, UPR and autophagy in flavivirus-infected cells and the growing evidences for an involvement of these cellular pathways in the replication and pathogenesis of these viruses.